Affirmative action in India: an alternative perspective - Mohanty, Amarnath (2007)
Explanations provided for the necessity of affirmative discrimination are basically fleshed out in two approaches, i.e. forward-looking and backward-looking. A critique of both these approaches is made in this paper followed by the construction of an alternative perspective from ideas derived from recent ethical theories which emphasise cross-time values, narrative perspective, historical context and organic unity. - Reproduced.
Keywords: Discrimination